Anaphylactoid reaction to dextran 40 during general anesthesia in two domestic pigs. (December 2021) - Yoshida, Kota
This report describes two cases of dextran-induced anaphylactoid reaction (DIAR), with and without cutaneous signs that appeared after administration of dextran 40 during general anesthesia in domestic pigs. Dextran was administered intravenously to 59 pigs that underwent general anesthesia for routine medical device training, and two pigs developed sudden, severe hypotension and decreased end-tidal CO2 level and arterial oxygen saturation within a few minutes after the start of dextran 40 infusion. A systemic cutaneous lesion presenting as flushing and urticaria was observed in case 1, whereas no skin lesions were found despite persistent observation in case 2. Cases 1 and 2 recovered with thoracic wall compression and an intravenous injection of epinephrine (0.02 mg) and hydrocortisone sodium succinate (250 mg). After DIAR treatment, no complications were observed, and the pigs were euthanized with an intravenous injection of thiopental sodium (1.0 g) when the training program was completed. This case report discusses the appearance of DIAR after dextran 40 administration during general anesthesia in domestic pigs, which is similar to DIAR in humans. However, the incidence of DIAR in this study was much higher than that in humans, suggesting that dextran 40 should not be used in domestic pigs.